Answers

2014-06-13T15:25:16+08:00
There are two possible answers, depending on how they transpose terms.

Lets remember the standard form of quadratic equations, that is Ax^2 + Bx + C = 0.

The given equation is:
5 - 3x = 2x^2

Transforming it to standard form by transposing all terms in the LEFT SIDE of the equation,we will have:

-2x^2 - 3x + 5 = 0

where a = -2 , b = -3 , c = 5 

Transforming it to standard form by transposing all terms in the RIGHT SIDE of the equation,we will have:

0 = 2x^2 + 3x - 5

where a = 2, b = 3, c = -5 

Conclusion both Edna and loisa are correct actually.
2 3 2